Mecanismos e obstáculos ao acesso pleno à tutela jurisdicional de mérito: uma abordagem jurídico-social - Cabral, Gustavo Varella (2006)
The object of this research that is the justification of this study is promoted a study about mechanism and instruments of access to rightness, essence and purpose to judicial Brazilian display, but not in your formal aspect, including therefore yours effects in society. In spit of advances passed away since Federal Constitution of 1988, mainly in substantive and formal rules, old obstacles are insisting to continue presents representing, during the process, problems that are increasing the number of judicial disputes instead of be them solutions. The modern rules, that pretending to render more easy and fair the access of rightness by the population, are prejudiced by obstacles that can’t be overcome by the judgements, leaving without expectations that become frustrations, increasing the number of judicial disputes. Nevertheless it’s obvious the Brazilian organized civil society’s effort, mainly of a lot of groups organized by law operators that are evaluating and searching ways to construct a better national system law, to find solutions to above-mentioned obstacles and to the new that are surging day by day. Brazil is a big group of values, races and cultures that tries, during his history, to construct a national identity based in practices adopted by others countries and societies. But the economical diversity of the members of this society and the different degrees of access to rightness are important factors to increase the largeness between Brazilians social classes. Pretentious was be a study about the components to this perverse equation. So we tried promote a study about the laws and the factors that are more important in judicial activity, manly reporting the access to rightness, delimiting ways to reduce the obstacles and to undervalue the price of the jurisdicional activity allowing the access to rightness of all Brazilian citizens. In this way, we will can reduce the largeness between Brazilian social classes in favor of legality, principles and 1988’s Constitutional warranties.